Time-of-day matters in text learning and recall: Evening lessons are advantageous for adults with ADHD though not for typical peers. (August 2022) - Sindiani, Mahmood; Korman, Maria; Karni, Avi
Abstract: Motor skill ("how-to" knowledge) consolidation is enhanced when individuals with ADHD practice at evening. We tested, in adults with and without ADHD, whether evening lessons are advantageous for recalling texts (declarative memory). Participants (N = 40) listened to and read narrative texts in morning and evening lessons (crossover study). Recall was tested immediately post-lesson and 24 h and 8–10 days later. Recall tended to decrease over time but independently of ADHD status or the time-of-day of the lesson. Nevertheless, typical participants showed a morning advantage immediately post-lesson and in later recall, correlated with stronger morning chronotype. In contrast, participants with ADHD benefited more from evening lessons; nearer their preferred time-of-day. In adults with ADHD long-term declarative memory was no less durable than in typical adults after both morning and evening lessons, but a mismatch with their preferred diurnal "on-peak" time can lead to less effective engagement in learning during morning lessons. Highlights: Persons with ADHD often struggle with learning and recalling new verbal materials. We show that these learning difficulties are related to the timing of the lesson. Typical adults better recall morning lessons; when they are at their daily peak. Adults with ADHD, more evening (on peak) chronotypes, recall evening lessons better. Evening or morning, there were no deficits in retention (8–10 days) in ADHD.